2023
DOI: 10.1186/s12967-023-04369-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction: roles in skeletal muscle atrophy

Abstract: Mitochondria play important roles in maintaining cellular homeostasis and skeletal muscle health, and damage to mitochondria can lead to a series of pathophysiological changes. Mitochondrial dysfunction can lead to skeletal muscle atrophy, and its molecular mechanism leading to skeletal muscle atrophy is complex. Understanding the pathogenesis of mitochondrial dysfunction is useful for the prevention and treatment of skeletal muscle atrophy, and finding drugs and methods to target and modulate mitochondrial fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 283 publications
2
23
0
Order By: Relevance
“…42,43 This evidence suggests an important role for the AMPK/Sirt1/PGC-1α signaling pathway in regulating mitochondrial biogenesis during exercise and that activation of this pathway reduces the negative effects of oxidative stress on skeletal muscle. 32 In the present study, we found that endurance exercise significantly delayed the age-related accelerated decline in climbing ability in Atg2 knockdown Drosophila. We also found that endurance exercise significantly increased AMPK/Sirt1/PGC-1α pathway activity significantly reduced muscle oxidative in Atg2 senescent Drosophila.…”
Section: Groupingsupporting
confidence: 54%
See 3 more Smart Citations
“…42,43 This evidence suggests an important role for the AMPK/Sirt1/PGC-1α signaling pathway in regulating mitochondrial biogenesis during exercise and that activation of this pathway reduces the negative effects of oxidative stress on skeletal muscle. 32 In the present study, we found that endurance exercise significantly delayed the age-related accelerated decline in climbing ability in Atg2 knockdown Drosophila. We also found that endurance exercise significantly increased AMPK/Sirt1/PGC-1α pathway activity significantly reduced muscle oxidative in Atg2 senescent Drosophila.…”
Section: Groupingsupporting
confidence: 54%
“…Cells lacking AMPK activity exhibit elevated mitochondrial ROS levels, increased oxidative damage, and premature senescence 42,43 . This evidence suggests an important role for the AMPK/Sirt1/PGC‐1α signaling pathway in regulating mitochondrial biogenesis during exercise and that activation of this pathway reduces the negative effects of oxidative stress on skeletal muscle 32 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, ROS contribute to the initiation of apoptosis through endoplasmic reticulum (ER) stress ( Liu et al ., 2022 ; Wang et al ., 2023 ). In particular, oxidative stress caused by insufficient removal of ROS, which occurs when muscles consume large amounts of oxygen for contractile activity, directly or indirectly affects muscle cell function and damages DNA and intracellular organelles ( Foreman et al ., 2021 ; Chen et al ., 2023 ). For example, ROS inhibits muscle differentiation from myoblasts to myotubes, promotes muscle atrophy through catabolism of differentiated muscle cells, and acts as a pathological cause of various muscle disorders ( Abrigo et al ., 2019 ; Alizadeh Pahlavani et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%